Multipotent mesenchymal stromal cells as treatment for poor graft function after allogeneic hematopoietic cell transplantation: A multicenter prospective analysis - Servais, Sophie; Baron, Frédéric; Lechanteur, Chantal; Seidel, Laurence; Baudoux, Etienne; Briquet, Alexandra; Selleslag, Dominik; Maertens, Johan; Poire, Xavier; Schroyens, Wilfried; Graux, Carlos; De Becker, Ann; et al. (Frontiers in Immunology, 2023)
Introduction Poor graft function (PGF) is a rare but serious complication of allogeneic hematopoietic cell transplantation (alloHCT). Due to their hematopoietic supporting properties and immune regulatory effects, multipotent mesenchymal stromal cells (MSC) could be considered a good candidate to help to restore bone marrow (BM) niches homeostasis and facilitate hematopoiesis after alloHCT. Methods We prospectively assessed the efficacy and safety of ex-vivo expanded BM-derived MSC from third-party donor in a series of 30 patients with prolonged severe cytopenia and PGF after alloHCT. This multicenter trial was registered at www.clinicaltrials.gov (#NTC00603330). Results Within 90 days post-MSC infusion, 53% (95% CI, 35 – 71%) of patients improved at least one cytopenia (overall response, OR) and 37% (95% CI, 19 - 54%) achieved a complete hematological response (CR: absolute neutrophil count, ANC >0.5 x 109/L, Hb > 80g/L and platelet count > 20 x 109/L with transfusion independence). Corresponding response rates increased to 67% (95% CI, 50 - 84%) OR and 53% (95% CI, 35 - 71%) CR within 180 days after MSC infusion. A significant decrease in red blood cells and platelets transfusion requirement was observed after MSC (median of 30-days transfusion requirement of 0.5 and 0 from d90-120 post-MSC versus 5 and 6.5 before MSC, respectively, p ≤0.001). An increase in ANC was also noted by day +90 and +180, with 3/5 patients with severe neutropenia having recovered an ANC > 1 x 109/L within the 90-120 days after MSC infusion. Overall survival at 1 year post-MSC was 70% (95% CI, 55.4 – 88.5), with all but one of the patients who achieved CR being alive. A single infusion of third-party MSC appeared to be safe, with the exception of one deep vein thrombotic event possibly related to the intervention. Discussion In conclusion, a single i.v. infusion of BM-derived MSC from third party donor seemed to improve hematological function after alloHCT, although spontaneous amelioration cannot be excluded. Comparative studies are warranted to confirm these encouraging results.